RETRACTION: Persistent Childhood Primitive Reflex Reduction Effects on Cognitive, Sensorimotor, and Academic Performance in ADHD - Melillo, Robert; Leisman, Gerry; Mualem, Raed; Ornai, Alon; Carmeli, Eli (Frontiers in Public Health, 2020)
A study was performed on 2,175 individuals between the ages of 3.2 and 22.04 years diagnosed with Attention Deficit Hyperactivity Disorder (ADHD) and drawn from 89 separate locations across the United States in satellite clinics with common practices and common staff training and equipment. The objective was to determine the efficacy of a hemispheric-based training program to reduce extant retained primitive reflexes (RPRs) and examine the relationship to motor function by metronome-based motor, DL and cognitive tasks measured by subtests of the Wechsler Wide Range Achievement Test. After a twelve-week program, RPRs were significantly reduced, as well as performance on all motor and cognitive measures significantly increased. Listening comprehension demonstrated significant increases between pre- and post testing of 7% (W = 1213000; df, 2094; p<0.0001) and mathematical problem solving revealed significant increase of 5% (W = 1331500; df, 2091; p<0.0001) associated with significant reduction in primitive reflexes. The study concluded that the incorporation of relatively simple hemispheric-based programming within the educational system worldwide could relatively inexpensively increase academic, cognitive and motor performance.